Effects of phosphorus-rich sawdust biochar sorption on heavy metals. Issue 17 (22nd November 2018) - Yang, Luo; Tan, Wen-fa; Mumford, Kathryn; Ding, Lei; Lv, Jun-wen; Zhang, Xiao-wen; Wang, Hong-qiang
ABSTRACT: The aim of this paper is to study the efficiency of typical heavy metals in electroplating sludge in terms of different phosphorus dosages (0.5 wt.%, 1 wt.% and 3 wt.%), initial pH (2, 3, 4, 5 and 6) and adsorption times (1, 3, 5, 7 and 12 h) of biochar. The heavy metal speciation was determined after adsorption to estimate the stability of ion-adsorption precipitation. Results show that phosphorus-modified biochar enhances the removal efficiency of heavy metals. Low mobility of heavy metal speciation was investigated. It is also shown that initial pH has a significant impact on the heavy metal speciation after adsorption.